2015
DOI: 10.5802/aif.2975
|View full text |Cite
|
Sign up to set email alerts
|

Polygonal Billiards with One Sided Scattering

Abstract: We study the billiard on a square billiard table with a one-sided vertical mirror. We associate trajectories of these billiards with double rotations and study orbit behavior and questions of complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Finally, in [ST15], the authors focused on a different part of the program suggested by Boshernitzan and Kornfeld. Namely, they studied billiards in rational polygons with so called spy mirrors and worked on the questions about complexity of the trajectories of these billiards.…”
Section: Results For Double Rotationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in [ST15], the authors focused on a different part of the program suggested by Boshernitzan and Kornfeld. Namely, they studied billiards in rational polygons with so called spy mirrors and worked on the questions about complexity of the trajectories of these billiards.…”
Section: Results For Double Rotationsmentioning
confidence: 99%
“…Connection with billiards. It was shown in [ST15] (using ideas from [BK95]) that double rotations can be considered as the first return map of the billiard flow for the so-called billiards with spy mirrors. This implies the following natural question, partly related to the problem of geometrical interpretation described above: is there a way to estimate the diffusion rate of the billiard trajectory in terms of the Lyapunov spectrum of the induction cocycle?…”
Section: Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Buzzi & P. Hubert (2004) [5], H. Bruin (2007Bruin ( ,2012 [3], S. Marmi, P. Moussa, J-C. Yoccoz (2012) [14], D. Volk (2014) [22]. A further generalization when a general cover is used instead of a special partition (which inevitably leads to a multi-valued map) was considered in A. Skripchenko & S. Troubetzkoy (2015) [18]. In any case the problem with the boundary points already mentioned in the case of IET is becoming a serious obstacle here.…”
Section: Historical Remarksmentioning
confidence: 99%
“…In the last years, there has been significant research on billiards in polygons [3,6,15,16,18,24,25]. Dynamics of these models is extremely difficult to rigorously analyze which often happens with systems with intermediate, neither regular (integrable) nor chaotic, behavior.…”
Section: Introductionmentioning
confidence: 99%